THE CONCEPT OF BOOK POSSESSION IN PROPERTY VINDICATION - ХАРЧЕНКО, Георгій (Київський національний університет імені Тараса Шевченка, 2025)
Background. Recently, the Supreme Court introduced the concept of book possession into the judicial practice of Ukraine, which significantly changed the previous approach to determining the criterion of a person's possession of real estate. This innovation is both supported and criticized by legal scholars. Naturally, there is a need to determine the feasibility of such changes, find their legal origins and reasons, and conduct a critical analysis for this purpose accordingly. Methods. To achieve the purpose of the study, the author used the following methods: formal and logical, dialectical, and comparative. Results. The author emphasizes that, in contrast to the traditional approach, when in cases of property vindication, possession was determined solely on the basis of the fact of physical possession of a thing, possession of real estate may be confirmed by the fact of state registration of the right to this property in accordance with the procedure established by law in the new concept of book possession.The change in the previous concept of property vindication has naturally changed the law enforcement practice of considering this category of court cases. Currently, in a situation where, for example, the property rights are registered to the plaintiff, and the de facto possessor of the property is the defendant, the Supreme Court sees the proper way of protection is not a vindicatory action, as it was before, but a negatory action, since the presence of an entry in the state register indicates, in the court's opinion, that possession of the property has not been violated.Such a paradigm shift has various consequences for law enforcement practice, particularly the fact that, according to the Supreme Court's conclusion, the statute of limitations does not apply to a negatory action. In contrast, the opposite is true for a vindicatory action. Conclusions. The concept of book possession eliminates the distinctions between vindicatory and negatory actions. It is not based on any provision of law. Still, it is a free and doctrinal interpretation of civil legislation by the Supreme Court, which, among other things, did not take into account the fact that the State register of real property rights to immovable property by law records a person's property rights to such asset, and not the fact of actual possession of it.

Вступ. Останнім часом у судову практику України Верховним Судом уведено концепцію книжкового володіння, яка істотно змінює попередньо існуючий підхід визначення критерію наявності в особи володіння нерухомим майном. Таке нововведення викликає як підтримку, так і критику з боку правознавців. Закономірно виникає потреба визначитись із доцільністю таких змін, з'ясувати їх правові витоки й причини та, відповідно, здійснити для цього критичний аналіз. Методи. Для досягнення мети дослідження використано такі методи, як формально-логічний, діалектичний, порівняльний. Результати. Зазначено, що, на відміну від традиційного підходу, коли при розгляді справ щодо віндикації майна володіння ним визначалось виключно на підставі факту фізичного утримання речі, у новій концепції книжкового володіння володіння нерухомим майном може бути підтверджене фактом державної реєстрації права на це майно в установленому законом порядку. Зміна попередньої концепції віндикації майна закономірно змінила правозастосовну практику розгляду цієї категорії судових справ. У ситуації, коли, наприклад, право власності зареєстровано за позивачем, а де-факто володільцем майна є відповідач, Верховний Суд вбачає належним способом захисту не віндикаційний позов, як це було раніше, а негаторний позов, оскільки наявність запису в державному реєстрі свідчить, на думку суду, що володіння майном не порушено. Така зміна парадигми має різні наслідки в правозастосовній практиці, зокрема через те, що на негаторний позов, за висновком Верховного Суду, позовна давність не поширюється, тоді як на віндикаційний позов – навпаки. Висновки. Концепція книжкового володіння нівелює відмінності між віндикаційним і негаторним позовами. Вона не базується на якійсь конкретній нормі закону, а є вільною і доктринальною інтерпретацією Верховним Судом цивільного законодавства, який, окрім іншого, не взяв до уваги, що в Державному реєстрі речових прав на нерухоме майно за законом фіксуються речові права особи на таке майно, а не факт реального володіння ним.
КОНЦЕПЦІЯ КНИЖКОВОГО ВОЛОДІННЯ ПРИ ВІНДИКАЦІЇ МАЙНА
Keywords: the concept of book possession; possession of property; vindicatory action; negatory action; state registration of property rights; концепція книжкового володіння; володіння майном; віндикаційний позов; негаторний позов; державна реєстрація речових прав